PERKAWINAN DI BAWAH UMUR DALAM PERSEPSI PELAKUNYA DI KECAMATAN CERME KABUPATEN GRESIK - Miyah, Nurul Isla; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2023)
Marriage is closely related to aspects of tradition, culture, economic factors, self-will, encouragement from parents, and so on. The results of the initial observations that the researchers made showed that couples who entered into underage marriages were due to various reasons, such as choosing to get married without coercion from their parents on the grounds that they love each other. There are also those who enter into underage marriages because they become pregnant out of wedlock as a result of promiscuity. The formulation of the problem in this research is how are the perceptions of underage actors about marriage. This study aims to reveal the perceptions of perpetrators of marriage about underage marriages. The focus of this research is to reveal the perceptions of underage actors about marriage. The basis of this research is the theory of Gestalt perception. The theory of perception is defined as the process of receiving stimulation through the advanced senses of an individual in selecting from information and experience which is then interpreted in order to make individual perceptions. The method applied to this research is descriptive qualitative research. The research informants were taken based on the classification, namely there were two underage marriage actors based on the economic level of the middle and upper families and pregnant out of wedlock, two perpetrators of underage marriages based on the level of higher education with the economic level of the middle and lower families, nine perpetrators of underage marriages based on love each other and the desire to marry at a young age, so that in this study 13 underage marriage actors were needed as key informants who married when they were under 20 years old. The location in this study was in Cerme District, Gresik Regency. Information collection techniques used are observation and in-depth interviews. The results of this study indicate that the perceptions of perpetrators of underage marriages are influenced by both internal and external factors. Internal factors are usually influenced by parental encouragement, self-will, or some things that require marriage to occur, such as getting pregnant out of wedlock. While external factors are influenced by peers, information media, community environment. The research results obtained from interviews with perpetrators who entered into underage marriages explained that the dream of having a beautiful marriage was wrong, after getting married of course there are many needs that make it stressful. There are some couples who think that getting married is so that their needs are met, but in fact some couples are of the view that after marriage there are many rules, marriage makes life prosperous. The suggestion in this study is that there is a need to socialize the age of marriage policy in Cerme District to parents in order to prevent conditions that can trigger their children to enter into underage marriages through meetings or at social gatherings for mothers in the Cerme District. Keywords: perpetrators, perceptions, underage marriages